The Use of Graphic Organizers in The Development of EFL Reading Comprehension - Llumiquinga, María Teresa (Kronos – The Language Teaching Journal, 2018)
This study investigated how the use of GOs helped EFL university students (18-22 years old) in the development of the reading comprehension skill. A control group and an experimental group participated in a pre-test and a post-test; the experimental group went through six reading activities which involved the use of GOs for reading comprehension. Additionally, a test to qualify their confidence in the use of GOs for ESL reading comprehension was applied to the experimental group. Results showed that the experimental group improved meaningfully from the pre-test to the post test.